Patterns and drivers of over-time change in the intergenerational transmission of inequality in Germany and the UK - Trinh, NA (2021)
This doctoral thesis contributes to research on over-time trends in the intergenerational transmission of inequality in two major European societies. Paper 1 entitled ‘Intergenerational Class Mobility of Labour Market Entrants in Germany and the UK since the 1950s’ shows that absolute mobility between parents’ social class and their children’s first social class has continuously changed. Still, increases in relative mobility rates have come to a halt for cohorts entering the labour market from the 1970s onwards in both countries. Paper 2 entitled ‘Why do Trends in Social Fluidity at Labour Market Entry and Occupational Maturity Differ? Evidence from Germany and the UK’ identifies increases in counter mobility as the main driver of observed divergence between trends in relative intergenerational social class mobility based on class destination measured at labour market entry and later career stages. It links the growth in counter mobility to compositional shifts in the origin distribution during the second half of the twentieth century. Paper 3 entitled ‘The Effect of Social Benefit Reform on Educational Inequality’ finds that children of parents receiving long-term unemployment assistance have a lower chance to attend the academic secondary school track compared to children of parents receiving no unemployment or social benefits after the 2005 Hartz reform in Germany. Besides changes in the socio-demographic characteristics of benefit recipients, this rise in educational inequality was mainly due to reductions in benefit levels. Paper 4 entitled ‘Parental Employment and Children’s Education in Historical Perspective’ shows that parental employment conditions have increasingly become economically insecure for cohorts born since the mid-1980s in Germany. No weakening in the positive association between parental employment and children’s education can however be observed.